Pitfalls and controversies in pathology impacting breast cancer management. Issue 3 (3rd March 2020) - Kim, Woo Gyeong; Cummings, Margaret C.; Lakhani, Sunil R.
ABSTRACT: Introduction : Breast cancer is a heterogeneous disease, at morphological, molecular, and clinical levels and this has significant implications for the diagnosis and management of the disease. The introduction of breast screening, and the use of small tissue sampling for diagnosis, the recognition of new morphological and molecular subtypes, and the increasing use of neoadjuvant therapies have created challenges in pathological diagnosis and classification. Areas covered : Areas of potential difficulty include columnar cell lesions, particularly flat epithelial atypia, atypical ductal hyperplasia, lobular neoplasia and its variants, and a range of papillary lesions. Fibroepithelial, sclerosing, mucinous, and apocrine lesions are also considered. Established and newer prognostic and predictive markers, such as immune infiltrates, PD-1 and PD-L1 and gene expression assays are evaluated. The unique challenges of pathology assessment post-neoadjuvant systemic therapy are also explored. Expert opinion : Controversies in clinical management arise due to incomplete and sometimes conflicting data on clinicopathological associations, prognosis, and outcome. The review will address some of these challenges.